Modeling crack initiation and propagation in nickel base superalloys - Korsunsky, A; Song, X; Belnoue, J; Prakash, L; Dini, D; Walsh, M (Trans Tech Publications Inc., 2007)
Nickel base superalloys are the primary class of materials used in the manufacture of high temperature components for gas turbine aeroengines, including combustion casings and liners, guide vane and turbine blades and dics, etc. These components are subjected to complex cyclic loading induced by the combination of mechanical loading, changing temperatures and thermal gradients, inducing plastic deformation and creep, that ultimately may lead to crack initiation and propagation. The purpose of the present paper is to provide a necessarily brief overview of recent modeling activities in this field, including polycrystalline crystal plasticity modeling for the study of crack initiation, coupled non-local damage-plasticity modeling for crack initiation and propagation studies, and the incorporation of time and environment dependent processes (creep and oxidation) in the predictive modeling of fatigue crack growth rates in nickel base superalloys).